PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH VARIETAS LEMBAH PALU (Allium wakegi Araki) DENGAN WAKTU TANAM BERBEDA DIANTARA TANAMAN CABAI SEBAGAI TANAMAN PAGAR - Rafik, Muhamad; Ansar, Muhammad (Fakultas Pertanian, Universitas Tadulako, 2024)
Lembah Palu shallot variety is a prominent commodity in Central Sulawesi, known for being a key raw material in the onion industry a regional trademark of Palu city. To enhance the shallot productivity, one effective strategy is the intercropping of shallots with chili plants, particularly with the F1 variety 'Dewa'. This study aimed to evaluate the growth and yield of Lembah Palu shallots when planted at different intervals relative to chili plants used as border crops. The research was conducted in Oloboju Village, Sigi Biromaru District, Central Sulawesi Province, from September to November 2019. The study employed a Randomized Block Design (RBD) with treatments based on different planting times of the shallots relative to the chili plants: T1 (simultaneous planting with chili), T2 (7 days after chili planting), T3 (14 days after chili planting), and T4 (21 days after chili planting). Each treatment was replicated four times, resulting in a total of 16 experimental plots. The results indicated that the different planting times of Lembah Palu shallots intercropped with chili plants did not significantly affect plant height, leaf number, or fresh root weight. However, significant effects were observed on the bulbdiameter and yield of Lembah Palu shallots.